CONSUMPTION OF THE GALING COMMUNITY ISLAMIC ECONOMIC PERSPECTIVES - Ferry Himatullah; Munadi; Ubabuddin (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2022)
This research departs from the phenomenon of Galing Village community is seen as a society with Middle-down economic conditions. This fact is inversely proportional to the consumption style of Galing villagers who tend to be consumptive and luxurious. This study uses a qualitative approach and type of case study research. Data collection techniques in this study were conducted by interview, observation, documentation. Data analysis techniques include: data reduction, data presentation, conclusion drawing. Data validity test is done by: extend participation, triangulation observation persistence, and member checking. Transferability test (certainty of data with detail), dependability test by auditing the research process and conformality Test Test the results of research (certainty of data) to draw conclusions. The results of this study indicate: first, the consumption of Galing villagers based on factors that affect consumption: income, number of family members, tastes, age, education level, environmental trends and religiosity have a positive effect on the consumption of Galing villagers. The income of each profession is influenced by the income of other professions. All professions have income tends to fluctuate except civil servants, therefore some professions get around it by looking for other income, saving, saving gold metal assets or debt to meet daily needs. the causes of the consumption style of the affluent and luxurious people; the former being a migrant worker or having a family being a migrant worker, looking for other income besides the main income characteristics of the upper class economy: priority needs are oriented towards future economic welfare, the lower economy: the main expenditure is to meet food needs and to increase non-investment assets Secondly, the phenomenon of consumption is contrary and in accordance with Abdul Mannan's 5 Principles of consumption ethics; not using formalin in accordance with the principle of Justice. Drug consumption, contrary to the principles of hygiene. Consumption of branded food and clothing is contrary to the principle of simplicity. Social alms at certain events according to the principle of generosity. Pray before work and work as a provision of worship in accordance with the principles of morality.